Resolving Atomic-Scale Defects in Conjugated Polymers On-Surfaces - Mallada, Benjamín; Chen, Qifan; Chutora, Taras; Sánchez-Grande, Ana; Cirera, Borja; Santos, José; Martín, Nazario; Ecija, David; Jelínek, Pavel; de la Torre, Bruno (Chemistry (Weinheim an der Bergstrasse, Germany), 2022)
Atomic scale defects significantly affect the mechanical, electronic, and optical properties of π-conjugated polymers. Here, isolated atomic-scale defects are deliberately introduced into a prototypical anthracene-ethynylene π-conjugated polymer, and its local density of states is carefully examined on the atomic scale to show how individual defects modify the inherent electronic and magnetic properties of this one-dimensional systems. Scanning tunneling and atomic force microscopy experiments, supplemented with density functional theory calculations, reveal the existence of a sharp electronic resonance at the Fermi energy around certain defects, which is associated with the formation of a local magnetic moment accompanied by substantial mitigation of the mobility of charge carriers. While defects in traditionally synthesized polymers lead to arbitrary conformations, the presented results clearly reflect the preferential formation of low dimensional defects at specific polymer sites, which may introduce the possibility of engineering macroscopic defects in surface-synthesized conjugated polymers.
Keywords: atomic force microscopy; on-surface synthesis; conjugated polymers; scanning tunneling microscopy